PENGARUH TINGKAT HUTANG (LEVERAGE) DAN PERSISTENSI LABA TERHADAP KUALITAS LABA PADA PERUSAHAAN PERHOTELAN, RESORT DAN CRUISE LINES YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Muhammad Fadhli; Iiz Izmuddin (CV. ADIBA AISHA AMIRA, 2024)
This research aims to analyze the impact of Debt Levels (Leverage) and Profit Persistence on the Profit Quality of Hotel, Resort and Cruise Lines companies listed on the Indonesian Stock Exchange (BEI) for the period 2018-2022. The population in this study is hotel, resort and cruise line companies listed on the Indonesian Stock Exchange (BEI). The research method used in this study is a quantitative method. This study uses an illustration of 9 hotel, resort and cruise line industry sectors listed on the Indonesian Stock Exchange (BEI) for the period 2018-2022 with a sample collection method using boredom sampling. The data analysis used in this study is descriptive statistical analysis, classical assumption experiments, multiple linear regression analysis, assumption experiments and limiting coefficient experiments using IBM SPSS 24. The elasticities used in this study are 2 types, namely free elasticities, namely debt levels (leverage) and profit persistence, and limited elasticities, namely profit quality. The results of this research partially prove that the elasticity of the debt level (leverage) has a significant effect on the quality of profits as evidenced by the experimental results of t count - 0.502 ≤ t table 2.018 with a significant figure of 0.618 ≥ 0.05. The elasticity of profit persistence has a significant effect on the quality of profits as evidenced by the t count - 2.802 ≤ t table 2.018 with a significant figure of 0.008 ≤ 0.05. The level of debt (leverage) and profit persistence simultaneously have a significant effect on the quality of profits as evidenced by the f count and f table figures 4.030 ≥ f table 3.22 with a significant figure of 0.025 ≤ 0.05